The DNA-remodelling activity of DnaD is the sum of oligomerization and DNA-binding activities on separate domains. - Carneiro, M; Zhang, W; Ioannou, C; Scott, D; Allen, S; Roberts, C; Soultanas, P (2006)
The Bacillus subtilis DnaD protein is an essential protein that has been implicated in the primosomal step of DNA replication, and recently in global DNA remodelling. Here we show that DnaD consists of two domains with distinct activities; an N-terminal domain (Nd) with oligomerization activity, and a C-terminal domain (Cd) with DNA-binding activity and a second DNA-induced oligomerization activity. Although Cd can bind to DNA and form large nucleoprotein complexes, it does not exhibit global DNA-remodelling activity. The presence of separate Nd does not restore this activity. Our data suggest that the global DNA-remodelling activity of DnaD is the sum of three separate oligomerization and DNA-binding activities residing on two distinct but linked domains.